Evaluation of infrared thermography, force platform and filmed locomotion score as non-invasive diagnostic methods for acute laminitis in zebu cattle. - Rejane Dos Santos Sousa; Francisco Leonardo Costa de Oliveira; Mailson Rennan Borges Dias; Natalia Sato Minami; Leonardo do Amaral; Antonio Humberto Hamad Minervino; Carolina de Lara Shecaira; Juliana Aparecida Bombardelli; Fernando José Benesi; Enrico Lippi Ortolani (PLoS ONE)
This study aimed to characterize oligofructose-induced laminitis in zebu cattle and comparatively evaluate four different diagnostic methods for laminitis. A total of 29 rumen-cannulated Nelore heifers, weighing 474.5 ± 58.5 kg were used. Laminitis was experimentally induced by intraruminal administration of 0.765 g/kg oligofructose twice daily for three consecutive days, followed by a single dose of 10.71 g/kg oligofructose on the fourth day. The animals were evaluated before administration of the highest dose of oligofructose (basal) and every six hours for up to 24 hours (6, 12, 18, 24 hours) and thereafter, every 12 hours for up to 72 hours (36, 48, 60, 72 hours) post-induction. The following diagnostic methods were used: hoof pain sensitivity test (hoof-testing), locomotion scoring, hoof infrared thermography, and force platform. Diagnosis of laminitis was confirmed after two positive responses to hoof pressure testing. Using a receiver operator characteristic (ROC) curve, we defined the appropriate cut-off for infrared thermography and force plate as 30 °C and < 24%, respectively. From the 29 heifers, 27 developed laminitis (93.1%) which occurred between 24 h to 72 h in the digits from two limbs, with more frequent sensitivity in the lateral digits. Locomotion analysis detected twenty-eight heifers with laminitis and showed that a greater (P = 0.006) number of animals had lameness in two limbs (n = 13; 56%). Using hoof-testing as gold standard for the diagnosis of laminitis the locomotion score displayed 100% sensitivity, 97% specificity and 98% accuracy; infrared thermography showed 96% sensitivity, 63% specificity, and 75% accuracy whilst force plate had 76% sensitivity, 82% specificity and 79% accuracy. This suggests that, for the diagnosis of laminitis in cattle, pain evaluation is more efficient. Considering the difficult to evaluate pain sensitivity in Nelore animals, filmed locomotion score, infrared thermography and force plate methods can be indicated for non-invasive lameness detection in beef farms.